2015
DOI: 10.1007/s00701-015-2355-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial atypical teratoid rhabdoid tumor: current management and a single institute experience of 15 patients from north India

Abstract: Median survival of 10 months reflects the aggressive biology of this rare neoplasm. Maximal safe resection followed by craniospinal irradiation and systemic chemotherapy with ICE or VAC regimen is a reasonable treatment strategy in this uncommon malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 25 publications
4
36
0
4
Order By: Relevance
“…However, these authors also state that, with a postoperative mortality rate of 4%, surgery may not be beneficial above receiving chemotherapy alone. Conversely, more recent work by Biswas et al and Lafay-Cousin et al suggest that CTR correlates with an increased 2-year survival from 21.7% (STR) to 60% (CTR) [7,22]. This is similar to the findings of the present study, which identified a trend toward increased survival with maximal resection (66.6% compared to 29% and 12.5% in the NTR and STR groups, respectively; Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, these authors also state that, with a postoperative mortality rate of 4%, surgery may not be beneficial above receiving chemotherapy alone. Conversely, more recent work by Biswas et al and Lafay-Cousin et al suggest that CTR correlates with an increased 2-year survival from 21.7% (STR) to 60% (CTR) [7,22]. This is similar to the findings of the present study, which identified a trend toward increased survival with maximal resection (66.6% compared to 29% and 12.5% in the NTR and STR groups, respectively; Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…3 Kaplan-Meier curves comparing survival of patients after CTR, NTR, and STR. Logrank test identified that greater resection was significantly associated with increased survival (p = 0.048) resection with increased survival [7,15,17,18,22,29]. Previous studies have estimated that 30% of patients will have metastatic disease at presentation, of which there is a higher incidence in patients less than 3 years old [12,29].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients can also present with cranial nerve palsies (cranial nerves VII and VIII) if cerebellopontine angle is involved by tumor. 28 30 …”
Section: Diagnosismentioning
confidence: 99%
“…An atypical teratoid/rhabdoid tumor is a rare disease with unfavorable outcome most commonly seen in children, although few cases of adult AT/RT have also been reported (20). Patient age at the time of diagnosis ranges between 7.2 months and 5 years (1,7,21,22,25,26,28); however, cases of in utero diagnosis have also been reported (4).…”
Section: █ Discussionmentioning
confidence: 99%